RANCANG BANGUN SISTEM PERINGATAN DINI DEMAM BERDARAH DENGUE (DBD) (Studi Kasus Demam Berdarah Dengue dan Curah Hujan di Wilayah Kota Jakarta Timur) - Muhammad Agung Prabowo; Hariyanto; Amir Mustofa Irawan (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
Dengue Hemorrhagic Fever (DHF) is a disease carried by the Aedes Agypti which is related with weather parameters that affect breeding and growth of mosquitoes, specifically the factors of humidity, temperature, and rainfall. East Jakarta is the city with the highest DHF risk in the DKI Jakarta Province every year. Dengue cases often occur during the rainy season and Dengue Fever Early Warning System (DHF) is needed to provide information to public for control and mitigation. This system is designed using a Tipping Bucket, DHT22 Sensor, SIM900A, RTC with solar power supply. The Dengue Hemorrhagic Fever Early Warning System uses Arduino Mega 2560 as a processing component. The data is sent to the server via the internet and displayed on Android applications and 20x4 LCDs, it is also stored on SD cards and online databases. The results of testing this instrument at the East Jakarta Pekayon District Office on November 30, 2019 – January 1, 2020, showed that the system was able to send data and provide measurement information and early warning information every day displayed on the Android application.